Experimental investigation for sequential triangular double-layered microchannel heat sink using nanofluids - Seder, Islam M.F (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
The heat generation in the electronic chips and microprossors needs a special and effective cooling system. Microchannel heat sink (MCHS), that offers a high heat transfer coefficient, is used to remove this heat where high thermal-conductive fluids such as water, oil and Nanofluids are employed rather than the limited removal heat capabilities of air heat sink. As it is well-known that configuration of MCHS has great impact on overall thermal performances; this study fabricated and tested innovative double-layered MCHS with triangular and rectangular shapes with using nanofluid as a coolant. A series of experimental runs for different channel dimensions and nanopartilce concentrations have been done. The result shows that double-layered MCHS outperforms traditional single-layer MCHS in thermal and hydrodynamic performances. Optimized sequential triangular double-layered MCHS provides a 27.4 % reduction in wall temperature comparing with initial guess and has better temperature uniformity across the channel length with less than 2°C. Sequential triangular shape also provides 16.6 % less total thermal resistance over rectangular shape at low pumping power. Enlarging the pumping power changes the location of the maximum base temperature to become near the inlet side of channel. Pressure drop observation shows no significant differences between triangular and rectangular shapes. Increasing the nanoparticle volume concentration Ø in the based fluid (Distill Water) causes a better thermal stability for both Al2O3-H2O and SiO2-H2O nanolfuids than pure water. 0.9 Ø Al2O3-H2O nanofluid experiences the best performances for the base thermal stability since the temperature different across the channel is 1.6 °C and the lowest thermal resistance is 0.13 °C/W.m2. This work suggests that one can adapt larger number of channel and smaller fin thickness to have less thermal resistance rather than only increasing the pumping power.